Dual disclosure of APOE genotyping and amyloid PET results to cognitively normal older adults: A qualitative analysis: Biomarkers (non‐neuroimaging)/Use in clinical trial design and evaluation. (7th December 2020) - Lee, Athene K.W.; Mandel, Nicolas; Popescu, Dominique; Williams, Randal; Alber, Jessica; Thompson, Louisa I.
Abstract: Background: Preclinical Alzheimer's disease (AD) is determined by biomarker risk assessment in cognitively normal individuals. Disclosure of risk is usually required for clinical drug trials targeting specific biomarkers (e.g., beta‐amyloid). More broadly, there is a growing movement towards participant engagement, which has fostered an interest in biomarker disclosure. Apolipoprotein‐E (APOE) genotype disclosure has been well researched, but less is known about dual disclosure of APOE and amyloid PET. Better understanding of how individuals and their families react to AD risk information will help refine the disclosure protocol. Method: Qualitative interviews were completed with 15 individuals (aged 61‐73) and 10 study partners who received APOE (all e4 carriers) and amyloid PET (5 positive) results as part of clinical trial screening. Interview transcripts were coded for motivation to learn, result comprehension, emotional/behavioral impact, and decision to share results. Analysis aims to characterize APOE vs. PET disclosure experiences between participants and partners. Result: Motivation included altruism, worries about developing AD, and access to new information and treatment. Amyloid PET was viewed as a natural follow‐up to APOE genotyping or part of a comprehensive risk assessment, not a distinct test. Interestingly, most participants had already decided to learn about APOE and amyloid PET before informing their spouses, and in the case that their spouses disagreed, invited friends as study partners. Participants and partners consistently comprehended APOE as a remote risk factor and amyloid PET as more reflective of imminent AD pathology. However, those with negative PET understood that amyloid levels change over time, questioned how close they were to the threshold, and hoped for a repeat evaluation in the future. Most partners remembered the APOE disclosure more vividly than PET. Participants reported no change in memory complaints or worries about future decline regardless of risk level. Spouses rarely expressed concerns about the participant's memory, were generally less worried about the results, and none observed memory changes after learning the risk level. Conclusion: Dual disclosure of APOE and amyloid PET appears to have minimal impact on perception of memory. Participants generally had stronger reactions to amyloid PET, while spouses had more vivid experience with APOE.